Incentivo à produç\~ao agroecológica e orgânica da agricultura familiar pelo programa de aquisiç\~ao de alimentos - Regina Helena Rosa Sambuichi; Gabriela Perin; Ana Flávia Cordeiro de Almeida; Rita Dicacia Felipe Câmara (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The Food Acquisition Program (PAA) is a federal government public procurement program created to support family farming and combat food and nutritional insecurity. This study analyzed the incentive provided by the PAA for agroecological and organic production in family farming, addressing the different mechanisms through which the program may be supporting this type of production among its beneficiary suppliers. To this end, a mixed-methods approach was adopted, using legal documents related to the public policy, administrative purchasing records from the program for the years 2012 to 2019, and primary field data collected through interviews with farmers from all Major Regions (GRs) of the country between 2021 and 2022. The analysis of the regulations showed that criteria were established to prioritize organic/agroecological farmers, with differentiated scoring for their proposals and the allowance for price premiums of up to 30% for these products. The results of the purchasing analysis indicate that these criteria were somewhat effective, especially in the case of the National Supply Company (Conab), as the percentage of purchases of these products by this operator increased from 1.8% in 2012 to 7.0% in 2019. The analysis of the prices showed that, in most cases, they were higher than the prices of conventional items - the increase was exactly 30% in 61% of cases. The interview results showed that the organic compliance process is still a challenge for most family farmers, as only 8.3% of those who accessed the PAA reported having some type of certification for organic products. It was also observed that the program offers other benefits to its suppliers, which are important for supporting agroecological and organic production, such as: facilitating access to other marketing channels; contributing to the improvement of product quality and diversity; providing more technical information to manage production and plan commercialization; and improving the food and nutritional security of its beneficiaries. These benefits, although not exclusive to agroecological and organic farmers, are crucial for supporting those who choose this type of production. However, the exclusion of the prioritization criteria for agroecological and organic farmers from the PAA regulations, starting in 2020, raises concerns about the continuity of the incentives identified in this research, highlighting the need to revise the regulations to ensure that these farmers remain a priority. Finally, it is recommended that future studies be conducted to further explore the observed aspects and identify the more recent effects of these changes.
Keywords: Q18; 330; public policies; food and nutrition security; organic and agroecological production